2018
DOI: 10.1097/dbp.0000000000000574
|View full text |Cite
|
Sign up to set email alerts
|

Raising Children with Autism Spectrum Disorders in Monolingual vs Bilingual Homes: A Scoping Review

Abstract: There is no evidence of a detrimental effect of raising children with ASDs in a bilingual home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 21 publications
1
21
1
Order By: Relevance
“…Research on the effects of raising a child with ASD in a bilingual environment is emerging; still, the majority of studies have focused on examining only language outcomes. Current literature demonstrates that infants with ASD, even those with intellectual disability, can acquire second language vocabulary (Hambly & Fombonne, 2014;Wang et al, 2018). Current literature also demonstrates that at school-age, 6-9-year-old children with ASD can become proficient bilinguals and follow similar language development patterns as typically developing bilingual children (Gonzalez-Barrero & Nadig, 2019).…”
Section: Bilingualism In Children With Asdmentioning
confidence: 98%
“…Research on the effects of raising a child with ASD in a bilingual environment is emerging; still, the majority of studies have focused on examining only language outcomes. Current literature demonstrates that infants with ASD, even those with intellectual disability, can acquire second language vocabulary (Hambly & Fombonne, 2014;Wang et al, 2018). Current literature also demonstrates that at school-age, 6-9-year-old children with ASD can become proficient bilinguals and follow similar language development patterns as typically developing bilingual children (Gonzalez-Barrero & Nadig, 2019).…”
Section: Bilingualism In Children With Asdmentioning
confidence: 98%
“…Research to date indicates that at worst bilingual exposure in children with ASD has no effect on language development and at best offers advantages on adaptive functioning, social communication, and receptive language (see Wang et al 3 for an in-depth review). Valicenti-McDermott et al 5 found that toddlers with ASD and bilingual exposure made increased attempts to communicate through gestures, cooing, and engaging in pretend play compared with their monolingual peers.…”
Section: Similarly Across Tasksmentioning
confidence: 99%
“…9 In addition, as has been reported for bilingual typically developing youngsters, bilingual children with ASD showed advantages on set-shifting tasks in cognitive tests. 3 However, as none of these advantages are consistently reported across the literature, the accepted view is that bilingual exposure in children with ASD has no detrimental effect on the child.…”
Section: Similarly Across Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…Research assessing executive functions, social cognition and language abilities of autistic people suggest no detrimental effects of bilingualism (e.g., Beauchamp and MacLeod, 2017 ), and some preliminary indications of positive effects (e.g., Valicenti-McDermott et al, 2013 ; Gonzalez-Barrero and Nadig, 2019 ; Montgomery et al, 2021 ), though more research is needed to quantify these claims. A detailed overview of the cognitive literature is outside the scope of this commentary, but see Drysdale et al ( 2015 ) and Wang et al ( 2018 ) for systematic reviews of this research.…”
Section: Introductionmentioning
confidence: 99%